Overview of Cognitive Function in The Elderly in Patrol Health Center Working Area Indramayu Regency - Dedeh Husnaniyah; Bestina Nindy Virgiani; Kamsari, Kamsari; Fina Anggraeni (HealthCare Nursing Journal, 2025)
The elderly experience major life changes such as changes in the nervous system, which can manifest as cognitive decline. The impact of decreased cognitive function such as decreased concentration, decreased level of awareness, disorientation of place and time, and unable to remember new things. The aim of this study was to determine the description of cognitive function in the elderly. This is a quantitative study with a descriptive approach, the population in this study were elderly people living in Patrol Village as many as 1,964, while the sampling technique used purposive sampling of 95 respondents. This instrument uses the MMSE questionnaire. Research shows that, as much as 46 respondents (48.4%) experienced moderate global cognitive function, 34 respondents (35.8%) experienced relatively good cognitive function, and 15 (15.8%) respondents experienced poor global cognitive function. The conclusion of this study description of cognitive function in the elderly in Patrol Village with moderate global cognitive function. This study it is hoped that health services will further improve socialization and programs, especially for the elderly to prevent a decrease in cognitive function.